-0.3(-0.06-3x)=5.5x

Simple and best practice solution for -0.3(-0.06-3x)=5.5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -0.3(-0.06-3x)=5.5x equation:


Simplifying
-0.3(-0.06 + -3x) = 5.5x
(-0.06 * -0.3 + -3x * -0.3) = 5.5x
(0.018 + 0.9x) = 5.5x

Solving
0.018 + 0.9x = 5.5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5.5x' to each side of the equation.
0.018 + 0.9x + -5.5x = 5.5x + -5.5x

Combine like terms: 0.9x + -5.5x = -4.6x
0.018 + -4.6x = 5.5x + -5.5x

Combine like terms: 5.5x + -5.5x = 0.0
0.018 + -4.6x = 0.0

Add '-0.018' to each side of the equation.
0.018 + -0.018 + -4.6x = 0.0 + -0.018

Combine like terms: 0.018 + -0.018 = 0.000
0.000 + -4.6x = 0.0 + -0.018
-4.6x = 0.0 + -0.018

Combine like terms: 0.0 + -0.018 = -0.018
-4.6x = -0.018

Divide each side by '-4.6'.
x = 0.003913043478

Simplifying
x = 0.003913043478

See similar equations:

| z+4(2+3)=15 | | 73-17+46= | | W/7-12=-1 | | -3x-24=x+8 | | x+.06x=106 | | (X-1)(x-2)+4=(x-1)+3 | | W/7-=-1 | | 2x^3-3x^2-x=0 | | 2x-37=x-5 | | 3(6-2x)+1=2(1x+2)-5x | | 0=4t+72 | | 1+-8z=-15 | | -y+6=11 | | 12x+5x=13x | | 2x-(x-5)=7-6(x-2) | | 48-6x=4x | | 5x+6y=6y+5x | | (9/10)*(4/5) | | -5x=4y+8 | | n+6=-16 | | 6s+s-4s-3s+4s=16 | | X^2+y^2+3x-2y=0 | | 5=3-(4-2) | | -4j-3j-j+j=20 | | 23=w+6 | | 1-2tan^2x=-tan^2x | | 0.25(y-4)+.03y=0.18y-0.05(40) | | j+j-j=11 | | -16t^2+84t+112=0 | | 6.3/0.9-(-4.1)x(-0.4) | | 8y-2(5+2y)=7y-16 | | 2 = 12(9x+8) |

Equations solver categories